2022
DOI: 10.1002/asia.202101399
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Selectivity Analysis of Fluorescent Probes for Hydrogen Sulfide Detection

Abstract: Hydrogen sulfide (H 2 S) is a gasotransmitter known to regulate physiological and pathological processes. Abnormal H 2 S levels have been associated with a range of conditions, including Parkinson's and Alzheimer's diseases, cardiovascular and renal diseases, bacterial and viral infections, as well as cancer. Therefore, fast and sensitive H 2 S detection is of significant clinical importance. Fluorescent H 2 S probes hold great potential among the currently developed detection methods because of their high sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…For further investigation, we detected the responsive release of H 2 S from TPP‐CN/CP5 in live bacterial cells using the H 2 S fluorescent probe Washington State Probe‐1 (WSP‐1). [ 18 ] After pretreating bacteria with different solutions and WSP‐1, the channel images of the H 2 S probe were monitored by fluorescence microscopy (Figure 3e ). As expected, almost no fluorescence was observed in the control group, and the bacteria exhibited weak fluorescence in the TPP‐CN/CP5 groups due to the release of a small amount of H 2 S triggered by endogenous Cys.…”
Section: Resultsmentioning
confidence: 99%
“…For further investigation, we detected the responsive release of H 2 S from TPP‐CN/CP5 in live bacterial cells using the H 2 S fluorescent probe Washington State Probe‐1 (WSP‐1). [ 18 ] After pretreating bacteria with different solutions and WSP‐1, the channel images of the H 2 S probe were monitored by fluorescence microscopy (Figure 3e ). As expected, almost no fluorescence was observed in the control group, and the bacteria exhibited weak fluorescence in the TPP‐CN/CP5 groups due to the release of a small amount of H 2 S triggered by endogenous Cys.…”
Section: Resultsmentioning
confidence: 99%
“…At 2.65 mM Na 2 S, we observed that 75% of the trophozoites were killed after one hour of exposure (Figure 1b). In order to monitor the H 2 S delivery into the parasite, we used fluorescent probe WSP-5 [48]. At a concentration of 2.65 mM Na 2 S, we observed a 1.4-fold increase in intracellular WSP-5 fluorescence compared to the untreated control trophozoites after 10 min of exposure.…”
Section: Exogenous H 2 S and Of Cys-ssh Induce Rapid Cytotoxicity In ...mentioning
confidence: 96%
“…As reported in our recent work, certain H 2 S fluorescent probes reported negligible responses to biothiols, while competing reactions between biothiols and H 2 S may still occur in complex biological samples. [206] Given the importance of H 2 S, clear discrimination between H 2 S, H 2 S mixtures with biothiols, and other signaling molecules should be accomplished.…”
Section: Design Challenges Of H 2 S Sensingmentioning
confidence: 99%